2013
DOI: 10.1186/1471-2342-13-28
|View full text |Cite
|
Sign up to set email alerts
|

Hysterosalpingocontrast sonography (HyCoSy): evaluation of the pain perception, side effects and complications

Abstract: BackgroundTubal and uterine cavity diseases commonly compromise female fertility. At the present time, hysteroscopy, laparoscopy with chromopertubation and RX-Hysterosalpingography (RX-HSG) are widely accepted screening procedures enabling the effective assessment of both tubal patency and uterine cavity. Nevertheless, consistent evidence supports the reliability of Hysterosalpingocontrast sonography (HyCoSy) in uterine cavity and tubal patency investigation, as a part of the standard infertility work-up. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…Most of women encounter pain in the course of the HyCoSy procedure [14][15][16]. Several studies have demonstrated the pain, side effects, and tolerability of HyCoSy, using a variety of materials for air microbubble suspensions [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of women encounter pain in the course of the HyCoSy procedure [14][15][16]. Several studies have demonstrated the pain, side effects, and tolerability of HyCoSy, using a variety of materials for air microbubble suspensions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the pain, side effects, and tolerability of HyCoSy, using a variety of materials for air microbubble suspensions [14,15]. Some investigators have evaluated the diagnostic accuracy of 4 D HyCoSy [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Mild to moderate pelvic pain has been reported in 24% to 35% of cases; vasovagal reactions, including nausea, pallor, faintness, and hypotension, occurred in less than 5% of cases; vaginal bleeding occurred in approximately 2% of cases; and fewer than 1% of patients experienced postprocedural infections. [3][4][5] To our knowledge, our case represents the first report of pneumoperitoneum as a complication of this procedure and adds to the body of literature about nonsurgical causes of free intraperitoneal air. The radiographic presence of free air usually represents visceral perforation in 85% to 95% of cases, but 5% to 15% of cases, as in our patient, have causes that do not require emergency surgery.…”
Section: Discussionmentioning
confidence: 57%
“…The ability of HyCoSy to detect tubal occlusion has been evaluated in other studies. There is good agreement between the results of HyCoSy and laparoscopy with dye with regard to tubal patency 19,20 , and HyCoSy is recommended as a screening method for tubal occlusion by the Royal College of Obstetricians and Gynaecologists in the UK (RCOG-NICE Clinical guidelines 21 ) and suggested by many as a first-line procedure in standard infertility work-up 18,22,23 . Moreover, laparoscopy with dye may yield false-positive results with regard to tubal occlusion 24 , just as HyCoSy may.…”
Section: Discussionmentioning
confidence: 98%